SCREENING PARADIGM FOR ?-THALASSEMIA CARRIERS; FROM CLINICAL TO MOLECULAR - Ibrahim Youssef; soha youssef; Galila Mokhtar; Mahira I. Elmogy; Hanan M. Mahmoud; maryse soliman ayoub; Shaimaa A. Pessar (Mediterranean Journal of Hematology and Infectious Diseases)
? thalassemia (?-thal) represents a major health problem worldwide and particularly in Egypt. Its prevention, when compared to treatment, is found to be cost-effective, possible and practical. This work aimed to evaluate the effectiveness of diagnostic techniques in detection of the ?-thalassemia carrier state.